The Effect of Academic Burnout and Quality of Life in Adolescents’ Career Indecisiveness - Anggraeni Kusumawardani; Dede Rahmat Hidayat (Universitas PGRI Yogyakarta, 2024)
Career decisions during adolescence are crucial and challenging. Most adolescents experience career indecisiveness, including dilemma, pressure, confusion, and difficulties which causes them to delay or leave their choices to others. Previous studies examined career indecision related to personality factors, social support, and school career programs. Aim of this study to examine the relationship and effect of academic burnout and quality on life towards career indecisiveness in adolescents. This quantitative study involved 575 adolescents in the Greater Jakarta area, which were selected through random sampling techniques. Data were collected by using google form questionnaires through a link. In this stage, the instrument consists of the Student Burnout Inventory, The WHO Quality of Life BREF, and The Career Indecisiveness Scale. Data were analyzed with multiple correlations and regression tests. The results showed that both academic burnout and quality of life have moderate correlations and effect in adolececnts’ career indecisiveness at 18.3%. The psycho-emotional dimension was a role in predicting academic burnout and quality of life, meanwhile the lack of information was a major problem for adolescents’ career indecisiveness. Keywords: adolescent, academic burnout, quality of life, career indecisiveness